Waveguide-Assisted Magneto-Optical Effects in 1D Garnet/Co/Au Plasmonic Crystals - Tatiana Murzina; Andrey Dotsenko; Irina Kolmychek; Vladimir Novikov; Nikita Gusev; Ilya Fedotov; Sergei Gusev (Photonics)
Magneto-plasmonic structures have been a subject of tremendous attention of researchers in recent decades as they provide unique approaches regarding the efficient control of optical, magneto-optical, and nonlinear-optical effects. Among others, magneto-plasmonic crystals (MPCs) have become one of the most studied structures, known for their high-quality tunable resonant optical properties. Here, we present the results of experimental and numerical studies on the functional magneto-optical (MO) response of planar 1D plasmonic crystals composed of Co/Au stripes of submicron period on the surface of a 3 μm thick rare-earth garnet layer. The experimental and numerical studies confirm that the wavelength–angular spectra of such structures contain a set of tunable resonant features in their optical and magneto-optical response, associated with the excitation of (i) surface plasmon polaritons at the Co/Au grating–garnet interface, as well as (ii) waveguide (WG) modes propagating in the garnet slab. A comparison of the MO effects in the transversal and longitudinal magnetization of the plasmonic structures is presented. We show that the most efficient Fano-type MPC magneto-optical response is realized for the WG modes of the first order for the longitudinal magnetization of the structure. Further perspectives regarding the optimization of this type of plasmonic crystal are discussed.